An overview of research literature on the management of development of university teacher training programs in the education field - Bouttavong, Phetdalaphone (International research journal of management, IT and social sciences, 2023)
This paper focuses on researching issues related to the management and development of teacher education programs at the university level. In the context of an ever-changing and complex society, the development of university teacher education programs becomes of utmost importance. These programs not only ensure a solid foundation of subject matter expertise but also aim to foster pedagogical skills, refine teaching abilities, and concurrently address the practical demands of the education sector. However, during the process of managing and advancing university teacher education programs, various issues and challenges have emerged. These encompass but are not limited to, updating teaching content in alignment with emerging trends, ensuring the applicability and practicality of knowledge, developing modern teaching methodologies, and integrating information technology into the learning process. Furthermore, establishing a dynamic learning environment and actively encouraging student participation are also noteworthy challenges. Additionally, ensuring that education programs meet the highest standards of quality and international benchmarks is a critical consideration. Hence, the research into issues related to the management and development of university teacher education programs becomes imperative. This endeavour seeks to examine deficiencies and gaps in the management process, thereby proposing specific and progressive solutions.